A Practical Method of Policy Analysis by Simulating Policy Options - James L. Phelps (Educational Considerations, 2011)
This article focuses on a method of policy analysis that has evolved from the previous articles in this issue. The first section, “Toward a Theory of Educational Production,” identifies concepts from science and achievement production to be incorporated into this policy analysis method.
Keywords: simulating; policy; options; educational; relevant; uncertainty principle; community; variable; achievement; theory